Long noncoding RNA HOTTIP contributes to the progression of prostate cancer by regulating HOXA13 - Zhang, S-R; Yang, J-K; Xie, J-K; Zhao, L-C (Cellular and Molecular Biology, 2016)
Prostate cancer is a leading cause of cancer-related mortality in men worldwide and there is a lack of effective treatment options for advanced (metastatic) prostate cancer. Long non-coding RNAs (lncRNAs) play important roles in diverse biological processes, such as cell growth, apoptosis and migration. However, little is known about the molecular mechanism of lncRNA-HOTTIP-mediated prostate cancer cell proliferation and apoptosis. The aim of this study was to elucidate the involvement of lncRNA HOTTIP in prostate cancer tumorigenesis and further investigate the role of HOXA13 in this process. Here, we showed that HOTTIP silencing inhibited cell survival pathway in vitro and in vivo by reducing the protein expression of Bcl-2 and enhancing Bax. We further demonstrated that knockdown of HOTTIP inhibited the expression of cell cycle regulatory protein Cyclin D1 and induced cell cycle arrest in G0/G1 phase. Additionally, depletion of HOXA13 by RNA interference (si-HOXA13) revealed that HOTTIP silencing suppressed cell growth at least partly through regulating HOXA13. In conclusion, down-regulation of HOTTIP and HOXA13 was associated with cell growth and cell cycle, and exerts tumor-suppressive functions in the genesis and progression of prostate cancer, providing a potential attractive therapeutic approach for this malignancy.